2022
DOI: 10.31436/imjm.v21i3.2047
|View full text |Cite
|
Sign up to set email alerts
|

Islam, Iman, and Ihsan: The Role of Religiosity on Quality of Life and Mental Health of Muslim Undergraduate Students in Islamic University

Abstract: INTRODUCTION: The current study examines the relationships between religiosity, quality of life, and positive mental health among Muslim students in an Islamic university in Malaysia. This study uses the operational definition of religiosity based on Hadith Jibril, which defined Islam into three elements: Islam, Iman, and Ihsan. Materials and Methods: One hundred and seventy-nine students participated in this cross-sectional study. Three measures were used to measure religiosity (IIUM Religiosity Scale), quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Additionally, this review also found confidence to the utility of religiosity specific to health services; where evidence was found to support the significance of Islamic input in improving the knowledge, skill, and attitude of future doctors who serves community within the same belief system (Musa et al, 2022). Moreover, Islamic elements was also concluded to be beneficial when integrated into psychological intervention and therapy as noted in Tajul Ariffin et al (2022); Misran et al (2021) studies.…”
Section: Implication Of the Reviewmentioning
confidence: 61%
See 2 more Smart Citations
“…Additionally, this review also found confidence to the utility of religiosity specific to health services; where evidence was found to support the significance of Islamic input in improving the knowledge, skill, and attitude of future doctors who serves community within the same belief system (Musa et al, 2022). Moreover, Islamic elements was also concluded to be beneficial when integrated into psychological intervention and therapy as noted in Tajul Ariffin et al (2022); Misran et al (2021) studies.…”
Section: Implication Of the Reviewmentioning
confidence: 61%
“…Evidently, multiple studies included in this review suggested caution especially when generalizing information (Ariffin et al, 2022;Foo et al, 2014;Francis et al, 2019;Che Rahimi et al, 2021;Misran et al, 2021;Zakaria et al, 2020;Mohammadi et al, 2020;Katmon et al, 2020;Sallam et al, 2018; which could largely be accounted by the sampling strategies employed by the studies. In this regard, Musa et al (2022) highlighted the necessity to conduct studies in various context, such as comparative studies between different groups, such as religious and non-religious groups (Mokhtar & Bahari, 2021), as well as between Gen-Y and/or Gen-X groups (Zakaria et al, 2020).…”
Section: Gaps and Limitation In The Literature Concerning Exploration...mentioning
confidence: 93%
See 1 more Smart Citation